Intravascular lymphoma presenting with postural hypotension. (29th January 2018) - Pearce, Catharine; Hope, Suzy; Butchart, Joseph
Abstract : An 84-year-old woman presented with severe postural hypotension. Further assessment revealed weight loss, fatigue and fever at night. On examination, she had bilateral skin lesions on the inner thighs and skin biopsy revealed intravascular high grade B cell lymphoma. This was successfully treated with curative chemotherapy. The cause of the postural hypotension in this case was felt likely to be autonomic neuropathy caused by neurovascular infiltration by intravascular lymphoma. Treatment of the lymphoma has resolved the postural hypotension, although some symptoms of postural instability persist.